Analysis of salt resistance conferred by salt overly sensitive 3 protein from mulberry (Morus notabilis) - Liu, Dan; Qiu, Changyu; Huang, Sheng; Lu, Xiaomei; Zeng, Yanrong; Zhu, Guangshu; Zhang, Chaohua; Lin, Qiang (Frontiers in Plant Science, 2026)
IntroductionSoil salinization severely threatens crop productivity and agricultural sustainability. Mulberry (Morus notabilis) is an economically important woody crop, but the molecular mechanisms of its salt tolerance remain unclear. The conserved Salt Overly Sensitive 3 (SOS3) gene regulates ion homeostasis under salt stress, making it a key target for exploring mulberry’s salt adaptation.MethodsWe cloned MnSOS3 from M. notabilis, constructed a prokaryotic expression vector (pCold-TF-MnSOS3) for transformation into Escherichia coli BL21, and generated MnSOS3-overexpressing transgenic tobacco (Nicotiana benthamiana) via Agrobacterium-mediated transformation. Salt tolerance was evaluated in E. coli (0.6 M NaCl) and tobacco (300 mM NaCl), with Na⁺/K⁺ content quantification in tobacco leaves (250 mM NaCl, 24 h) and verification of MnSOS3-MnSOS2 interaction via yeast two-hybrid assay.Results and discussionRecombinant E. coli expressing MnSOS3 showed enhanced growth (maximum OD₆₀₀ = 0.338) vs. near-zero growth in the control. Transgenic tobacco line MnSOS3-2 (highest expression) exhibited 33.3% survival under 300 mM NaCl, 2.5-fold higher than wild-type (WT, 13.3%). Transgenic leaves accumulated 54.8% less Na⁺ (0.95 ± 0.02 vs. 2.10 ± 0.07 mmol/g FW) and 45.8% more K⁺ (1.75 ± 0.02 vs. 1.20 ± 0.02 mmol/g FW) than WT, leading to a 67.8% lower Na⁺/K⁺ ratio (0.55 ± 0.01 vs. 1.71 ± 0.08). The yeast two-hybrid assay confirmed MnSOS3-MnSOS2 interaction. These findings show MnSOS3 boosts salt tolerance via Na⁺/K⁺ homeostasis and SOS pathway activation, a key resource for salt-tolerant mulberry breeding.